Harold Persico Paris. - Wurster, Robert Michael (Brussel : Galerie Withofs, 1970)
(Brussels, 1970), square in-4°, 23 x 23 cm, ca. 40 nn pp, sewn, original wrapper. The catalogue is perforated in the centre with a hole in the form of an eye (diameter 5 cm), tipped in is a plastic eyelash. The text by Wurster is in English and also translated in French and Dutch.
Harold Persico Paris, Galerie Withofs, Brussel, 15 januari tot 7 februari 1970
Frans & Nederlands & Engels
kunstcatalogus
Keywords: Persico Paris, Harold